2014
DOI: 10.1148/radiol.14131903
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Volumetric Measurements in Stage I Lung Adenocarcinoma

Abstract: Two volumetric measurements (solid volume, ≥1.5 cm(3); percentage of solid volume, ≥63%) were found to be independent indicators associated with increased likelihood of recurrence and/or death in patients with stage I adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…These slice thickness differences were thought to be one of the reasons for the discrepancies in the results. Further, other reports have shown that the degree of solid component on chest CT was more highly relevant to the pathological invasiveness and prognosis than the total tumor size [22][23][24], whereas our results showed that SUVmax was a more reliable predictive factor of visceral pleural invasion than the solid component size and ratio on HRCT. In fact, SUVmax contributed the most to the multivariate models, and the present study demonstrated that the diagnostic performance for visceral pleural Nonetheless, the present study has certain limitations.…”
Section: Discussioncontrasting
confidence: 82%
“…These slice thickness differences were thought to be one of the reasons for the discrepancies in the results. Further, other reports have shown that the degree of solid component on chest CT was more highly relevant to the pathological invasiveness and prognosis than the total tumor size [22][23][24], whereas our results showed that SUVmax was a more reliable predictive factor of visceral pleural invasion than the solid component size and ratio on HRCT. In fact, SUVmax contributed the most to the multivariate models, and the present study demonstrated that the diagnostic performance for visceral pleural Nonetheless, the present study has certain limitations.…”
Section: Discussioncontrasting
confidence: 82%
“…The volume of the solid part of the lung carcinoma and the solid part ratio were reported as independent indicators of prognosis in stage I adenocarcinoma patients treated with surgery. 33 Though the method of volume measurement was different, these results are consistent with our study. Other authors reported a correlation between ATN and prognosis in patients with small pulmonary adenocarcinomas.…”
Section: Discussionsupporting
confidence: 91%
“…This demonstrates the importance of separating the computerized analyses of CT regions from GGO and solid components to assess adenocarcinoma cancer aggressiveness. 24 A majority of studies focused on the ratio of GGO and solid quantities, 5,11,12,[14][15][16] whereas our work provides a novel perspective on how to interpret imaging information from CT examinations by suggesting that most of the information related to adenocarcinoma aggressiveness is located in the solid components of the tumor.…”
Section: Discussionmentioning
confidence: 95%